Are women underrepresented in the American statistics profession?. Issue 2 (April 2016) - Golbeck, Amanda
Abstract : Amanda Golbeck digs into the Annual Survey of the Mathematical Sciences in search of an answer Abstract : Are women underrepresented in the American statistics profession? Amanda Golbeck goes in search of an answer